2010
DOI: 10.1063/1.3291072
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional vorticity measurements in the wake of a yawed circular cylinder

Abstract: Using a phase-averaged technique, the dependence of the wake vortical structures on cylinder yaw angle ␣ ͑=0°-45°͒ was investigated by measuring all three-velocity and vorticity components simultaneously using an eight-hot wire vorticity probe in the intermediate region ͑x / d =10͒ of a yawed stationary circular cylinder wake. For all yaw angles, the phase-averaged velocity and vorticity contours display apparent Kármán vortices. It is found that when ␣ Յ 15°, the maximum coherent concentrations of the three v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…whereas the root-mean-square lift coefficients violated the IP when θ > 30º for Re = 1000, which was also observed by Lam et al (2010). Zhou et al (2010) observed that the secondary axial vortices were generated in the cylinder wakes and the three dimensionality of the flow was enhanced when θ was larger than 15°. As for a stationary near-wall cylinder, Thapa et al (2014) showed that the IP applied to the flow at the gap ratio of 0.8 better than that at 0.4 for Re = 500.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…whereas the root-mean-square lift coefficients violated the IP when θ > 30º for Re = 1000, which was also observed by Lam et al (2010). Zhou et al (2010) observed that the secondary axial vortices were generated in the cylinder wakes and the three dimensionality of the flow was enhanced when θ was larger than 15°. As for a stationary near-wall cylinder, Thapa et al (2014) showed that the IP applied to the flow at the gap ratio of 0.8 better than that at 0.4 for Re = 500.…”
Section: Introductionsupporting
confidence: 64%
“…Particular attention has been paid to the validity of the IP for a stationary wall-free cylinder in estimating the force coefficients and the Strouhal number St (e.g. Ramberg, 1983;Zhao et al, 2009;Lam et al, 2010;Zhou et al, 2010). The Strouhal number is defined as St = f 0 /U 0 D, where f 0 is the vortex shedding frequency.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of rigid and vertical beams (θ ≡ 0), (2.4) reduces to the formulation used in Singh et al (2016). We refer readers to Zhou et al (2010) for a more extensive review of drag on tilted cylinders.…”
Section: Equations For the Fluidmentioning
confidence: 99%
“…13 With regard to the variation of Strouhal number St (≡fD/U, where f is the vortex shedding frequency) with Reynolds number, two discontinuities occur when the flow changes from 2D laminar flow to mode A and from mode A to mode B, respectively. 3,7 Flow around an inclined circular cylinder has also been investigated extensively both experimentally [14][15][16][17][18][19] and numerically [20][21][22][23] in the past few decades. In engineering practice, the independence principle (or the cosine law) is commonly employed to predict the hydrodynamic forces and vortex shedding frequency of an inclined circular cylinder.…”
Section: Introductionmentioning
confidence: 99%